2017
DOI: 10.21608/agro.2017.662.1058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium on Growth, Physiological Aspects and Productivity of Faba Bean (Vicia faba L.)

Abstract: T HIS WORK was conducted during the two successive winter seasons of 2014/ 2015 and 2015 / 2016 at the Agricultural Experiments and Researches Station (Ghazala Farm), Faculty of Agriculture , Zagazig University , Sharkia Governorate, Egypt, to study the effect of foliar spray with selenium at concentrations of 0, 2.5 , 5 , 10 , 15 and 20 ppm on growth, chemical composition , yield as well as anatomy of stem and leaves of faba bean cv. Giza 716. The experimental results showed that foliar application with 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
13
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
8
13
1
2
Order By: Relevance
“…Also, Selenium like heavy metals can modify uptake and accumulation of minerals which are important for plant metabolism (Pazurkiewicz-Kocot et al 2003). Our results are in agreement with those of Boghdady et al (2017) and Shedeed et al (2018). In this context, tubers containing high percentages of Br and Se provide a vital elements for human and animal i.e.…”
Section: Tuber Nutrient Contentssupporting
confidence: 94%
See 1 more Smart Citation
“…Also, Selenium like heavy metals can modify uptake and accumulation of minerals which are important for plant metabolism (Pazurkiewicz-Kocot et al 2003). Our results are in agreement with those of Boghdady et al (2017) and Shedeed et al (2018). In this context, tubers containing high percentages of Br and Se provide a vital elements for human and animal i.e.…”
Section: Tuber Nutrient Contentssupporting
confidence: 94%
“…The other treatments achieved an intermediate average value. The obtained results are in parallel, more or less, with those recorded by Bari et al (2001), Boghdady et al (2017), Muthanna et al (2017) and Shedeed et al (2018). Plant height increment could be accounted for the mode of action of Br and Se physiological promotive effects which enhance plant photosynthetic activity and concomitant vigour plant growth (Nowak et al, 2010;Chu et al;Yao et al, 2010).…”
Section: Vegetative Growthsupporting
confidence: 90%
“…In this respect, Smolen et al [17] demonstrated that I and Se did not affect lettuce yield. The biofortification of beans with Se revealed that seed yield largely depended on Se dose, ranging from zero up to a 1.7-fold increase [37]. A similar phenomenon has been reported for plant biofortification with I [38].…”
Section: Root Mycorrhizal Colonization Yield Growth and Biometricasupporting
confidence: 74%
“…Foliar application of selenium led to increased absorption of N, P, K, Ca and Mg and decreased absorption of Na and Cl under salt stress conditions. Boghdady et al (2017) found that foliar spraying with selenium at low concentrations had a positive effect on a significant increase of N, P and K percentage in faba bean seeds.…”
Section: Leaves Mineral Contentmentioning
confidence: 92%